Evaluation of Land Information System Development in The National Land Agency - Fahmi Charish Mustofa (Pusat Penelitian dan Pengabdian kepada Masyarakat, Sekolah Tinggi Pertanahan Nasional, 2020)
The development of information and communication technology creates opportunities to provide a more reliable and efficient Land Information System (SIP). Users of land data and information demand the provision of good land information services. The Ministry of Agrarian Affairs and Spatial Planning/National Land Agency (Kementerian ATR/BPN) as a government agency providing land information services has tried to accommodate these demands. Since several decades ago the development of SIP has been carried out. There is a lack number of research paper documented the development of SIP within Kementerian ART/BPN, so the aim of this paper is to documenting the development.The critical analysis approach used is based on the Information System Structure Theory, System Development Life Cycle (SDLC) and Geographic Information System Enterprise Technology (GIS), which are used as an evaluation approach to SIP development in Kementerian ATR/BPN. The results of this study provide portraits of SIP from various perspectives and underline some of the opportunities and challenges of developing SIP in the future.Keywords: Land Information System, Information System Structure, System Development Life Cycle, Enterprise GISIntisari: Perkembangan teknologi informasi dan komunikasi membuka peluang untuk menyediakan Sistem Informasi Pertanahan (SIP) yang lebih handal dan efisien. Pengguna data dan informasi pertanahan menuntut penyediaan layanan informasi pertanahan yang baik. Kementarian Agraria dan Tata Ruang/Badan Pertanahan Nasional (Kementerian ATR/BPN) sebagai lembaga pemerintah penyedia layanan informasi pertanahan telah berusaha mengakomodasi tuntutan tersebut. Sejak beberapa dekade silam pengembangan SIP telah dilaksanakan. Tidak banyak dokumentasi berupa paper ilmiah yang merekam pengembangan SIP di lingkungan Kementerian ART/BPN. Paper ini disusun dengan tujuan mendokumentasikan perjalanan pengembangan tersebut disertai ulasan kritis berdasar teori-teori pengembangan sistem. Pendekatan analisis kritis yang digunakan bersifat deskriptif kualitatif berdasar Teori Struktur Sistem Informasi, System Development Life Cycle (SDLC) dan Teknologi Enterprise Sistem Informasi Geografis (SIG), yang digunakan sebagai pendekatan evaluasi pengembangan SIP di Kementerian ATR/BPN. Hasil penelitian ini menjelaskan SIP dari berbagai perspektif dan menggarisbawahi beberapa peluang dan tantangan pengembangan SIP di masa yang akan datang.Kata kunci: Sistem Informasi Pertanahan, Struktur Sistem Informasi, System Development Life Cycle, Enterprise SIG